Clunk-click every trip. (Economist, 1995)
Discusses several aspects of France's Minitel terminal and states that, despite many problems, it has gone farther than the Internet in testing what ordinary people want from computer networks. Number of Minitel terminals in France in 1995; Interactive information services; Actions by France Telecom, owner of Minitel.